Are you being served? : new tools for measuring service delivery - Amin, Samia, 1980-; Das, Jishnu; Goldstein, Markus P., 1970- (World Bank e-Library., 2008)
This publication presents tools and techniques for measuring service delivery in health and education and people's experiences from the field in deploying these methods. It begins by providing an introduction to the different methodological tools available for evaluating the performance of the health and education sectors. Country specific experiences are then explored to highlight lessons on the challenges, advantages and disadvantages of using different techniques to measure quality in a variety of different contexts and of using the resulting data to affect change. This book is a valuable r.